FACTORS INFLUENCING ANTENATAL CARE (ANC) VISITS AT THE BABAH BULOH PUBLIC HEALTH CENTER, SUB-DISTRICT SAWANG, NORTH ACEH REGENCY IN 2025: Factors Influencing ANC Visit - Nilawati Nilawati (Journal of Midwifery and Community Health (JMCH), 2026)
Background: Pregnancy and childbirth complications, as the leading cause of maternal mortality, can be prevented through regular pregnancy check-ups known as antenatal care (ANC). In Indonesia, there are nearly 20,000 cases of maternal death due to complications during pregnancy and childbirth every year. The mortality rate for toddlers has reached the 2030 Sustainable Development Goal (SDG) target of 25 per 1,000 live births. The percentage of K4 in the North Aceh district in 2024 is 84.6%. The objective of this study is to find out the factors influencing visits to antenatal care (ANC) at the Babah Buloh Health Center, Sub-district Sawang, North Aceh Regency in 2025 Subjects and Method: This study is a quantitative, cross-sectional study. The sample in this study comprised all pregnant women who attended antenatal care visits at the Babah Buloh Health Center, Sawang District, North Aceh Regency, a total of 105 women. Results: The results of the statistical test on the influence of knowledge, attitude, husband support, and health worker support on antenatal care (ANC) visits in pregnant women were obtained with p-value values = (0.007), (0.000), (0.000), and (0.000), which means that there is an influence on 4 independent variables on the dependent variables. Conclusion: There is an influence between knowledge, attitudes, husband support, and health worker support on antenatal care (ANC) visits in pregnant women at the Babah Buloh Health Center, Sawang District, North Aceh Regency Keywords: Antenatal care (ANC), Knowledge, Attitude, Husband Support, Health Worker Support.